(untitled) (Journal of Foreign Language Studies, 2019)
Le Dat is one of the poets who have made great contributions to the innovation of contemporary Vietnamese poetry, especially in terms of the Vietnamese language. He emphasized that each poet must be a “phu chu”, the word used by the poet to define whoever devotes his life to word-making, because he believed that “a poet is honored for his words”. Poetry writing, for Le Dat, is an experiment with words or a word game which is the most effective way of making new meanings, enriching the Vietnamese vocabulary and expressing his style and creativity. In his poetry collection - “Shadow of Words”, he rejected the form of the traditional poetic language and showed the strong and acute sense of creating a new language form.